2011
DOI: 10.1016/j.jcis.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic quantities of surface formation of aqueous electrolyte solutions X. Aqueous solution of 2:1 valence-type salts

Abstract: The behaviors of a series of calcium halides and of alkali earth metal chlorides in the air/water surface region were studied in comparison with those of alkali metal halides by measuring the surface tension increments of solutions. The effect of salts with divalent cation on the surface tension increments is pronounced than that of uni-univalent salts, but there are some similarities between these two types. It seems that the anions cause a marked effect on surface tension which is proportional to the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…A continuous increase or decrease in IFT trend was also reported at a relatively very high salt concentration (0.5–1.5 M for NaCl and KCl) in brine and large difference in salt concentration (0.5 M) between two consecutive trials for hydrocarbon–brine system . The increase in the trend of IFT for hydrocarbon–brine system was reported by other researcher as well. ,,, Lima et al justified that the abrupt behavior of IFT could be due to variable ionic size and chemical potential. Recently, one of our studies reported the impact of low salt concentration on the IFT of hydrocarbon–water system.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…A continuous increase or decrease in IFT trend was also reported at a relatively very high salt concentration (0.5–1.5 M for NaCl and KCl) in brine and large difference in salt concentration (0.5 M) between two consecutive trials for hydrocarbon–brine system . The increase in the trend of IFT for hydrocarbon–brine system was reported by other researcher as well. ,,, Lima et al justified that the abrupt behavior of IFT could be due to variable ionic size and chemical potential. Recently, one of our studies reported the impact of low salt concentration on the IFT of hydrocarbon–water system.…”
Section: Introductionsupporting
confidence: 54%
“…The reason for drop and rise of IFT was explained using the Gibbs adsorption isotherm. However, the conclusions drawn on the trend of IFT by various investigators 12,29,33 on hydrocarbon−brine system were not identical. The contradictory statements could be due to the consideration of different ranges of salt concentration by the investigators during their study.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The addition of electrolytes into pure water would increase the surface tension of the solutions (Jones and Ray 1941;Bostrom et al 2001;Ozdemir et al 2009;Matubayasi et al 2011;Holthusen et al 2012). These surface tension increments can be related to the force balance at the three-phase contact line formed by the drops of electrolyte solutions on the soil surfaces, and therefore to the contact angle.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the surface tension of water increases when inorganic salts (such as sodium chloride (NaCl), potassium chloride (KCl), sodium sulfate (Na 2 SO 4 ), calcium chloride, (CaCl 2 ), etc.) are dissolved (Jones and Ray 1941;Bostrom et al 2001;Ozdemir et al 2009;Matubayasi et al 2011;Holthusen et al 2012), while it decreases when organic substances (ethanol, methanol, fatty acids, soaps, detergents, etc.) are added.…”
Section: Introductionmentioning
confidence: 99%